Effect of drops on turbulence of kerosene-water two-phase flow in vertical pipe - Hamad, F.A.; Ganesan, P. (2015)
The effect of introducing kerosene drops on turbulence of kerosene-water two-phase in a vertical pipe is investigated experimentally. A hot-film and dual optical probes are used to measure the water velocity, turbulence fluctuation, drop relative velocity, volume fraction and drop diameter. Experiments are performed in a 78.8 mm diameter vertical pipe for four average water velocities of 0.11, 0.29, 0.44 and 0.77 m/s. The measurements were carried out for two area average volume fraction A of 4.6% and 9.2% as well as for water single phase flow to investigate the effect of introducing kerosene drops on two-phase flow turbulence. The kerosene-water mixture was generated by adding the kerosene to constant flow rates of water. The results indicate that drops induced turbulence is a function of the ratio of the drop Reynolds number (U(r)d(B)/v) to the turbulence Reynolds number (u'L-t/v) which decreased with higher water velocities. The results show that the Kolmogorov-Richardson scaling in the range of -4.5/3 to -6/3 for single phase flow which is replaced by -6/3 to -7/3 for two-phase flow. These values are less than -8/3 for air-water flow. (C) 2015 Elsevier Inc. All rights reserved.